INTESTINAL SYNDROME DURING VIRAL INFECTIONS IN CHILDREN, THE PROSPECTS FOR TREATMENT - M. S. Savenkova (LLC "Diagnostics and Vaccines", 2015)
The article presents the history of the study of intestinal lesions of viral origin. The literature data was generalized, which regarding changes in the gastrointestinal tract viral infections transmitted not only by the fecal-oral route, but also airborne. The description of the clinical picture of viral infection of the intestine, morphological data, new approaches to treatment was presented.